2017
DOI: 10.3389/fneur.2017.00297
|View full text |Cite|
|
Sign up to set email alerts
|

Dedifferentiation Does Not Account for Hyperconnectivity after Traumatic Brain Injury

Abstract: ObjectiveChanges in functional network connectivity following traumatic brain injury (TBI) have received increasing attention in recent neuroimaging literature. This study sought to understand how disrupted systems adapt to injury during resting and goal-directed brain states. Hyperconnectivity has been a common finding, and dedifferentiation (or loss of segregation of networks) is one possible explanation for this finding. We hypothesized that individuals with TBI would show dedifferentiation of networks (as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 48 publications
7
26
1
Order By: Relevance
“…First, like most all studies in this literature, TBI is a heterogeneous disorder and ideally we would have a sample size that permitted subgroups for analysis. While the current data demonstrated the within subject reliability of network dynamics and the sample size here is comparable to prior graph theory analysis examining static networks after moderate and severe TBI [ 4 , 6 , 7 , 68 ], the sample size for this study does preclude direct examination of the reliability of these findings with respect to the groups (e.g., split-half reliability). For this reason, replication of the current findings is needed in a separate group of individuals with moderate and severe TBI with focus on the primary findings: 1) network dynamic loss (i.e., reduced state transitions), 2) occurrence of rare states not evident in the healthy adults in this sample.…”
Section: Discussionsupporting
confidence: 60%
“…First, like most all studies in this literature, TBI is a heterogeneous disorder and ideally we would have a sample size that permitted subgroups for analysis. While the current data demonstrated the within subject reliability of network dynamics and the sample size here is comparable to prior graph theory analysis examining static networks after moderate and severe TBI [ 4 , 6 , 7 , 68 ], the sample size for this study does preclude direct examination of the reliability of these findings with respect to the groups (e.g., split-half reliability). For this reason, replication of the current findings is needed in a separate group of individuals with moderate and severe TBI with focus on the primary findings: 1) network dynamic loss (i.e., reduced state transitions), 2) occurrence of rare states not evident in the healthy adults in this sample.…”
Section: Discussionsupporting
confidence: 60%
“…With respect to the meaning of the enhanced response observed in state 3, increased regional brain response commonly observed during goal directed behavior in neurological disorders, and even during normal aging, has been historically interpreted as neural compensation (Hillary et al, 2006; Dennis & Cabeza, 2008) or scaffolding (Park et al, 2009). More recently, this finding has been extended to studies of network dynamics (Bernier et al, 2017; Medaglia et al, 2017). Based upon this explanation, the posterior connectivity loss observed in the MCI literature would be bolstered by greater anterior connectivity representing enhanced support via cognitive control (Hillary et al, 2006).…”
Section: Discussionmentioning
confidence: 75%
“…Meanwhile, our previous study used GCA to analyze the causal connections in the acute mTBI patients and demonstrated significantly increased connectivity from the left ACC to the left MFG 34 . For mTBI patients, Benier et al and Sharp et al hypothesized that such hyperconnectivity patterns in the DMN could be related to dysfunction in working memory and attention switching during cognitive demand 35,36 . MFG connectivity appeared to be associated with the degree of language deficit, a finding supported by the notion of increased use of MFG neural resources as a compensation for impaired neural cognitive function.…”
Section: Discussionmentioning
confidence: 77%